2017
DOI: 10.1007/s00436-017-5518-7
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence and risk factors of Toxoplasma gondii infection in invasive raccoons (Procyon lotor) in Central Europe

Abstract: Toxoplasma gondii is an obligate intracellular protozoan that causes toxoplasmosis in warm-blooded animals. Most mammals, including humans, can become intermediate host, resulting in subclinical infection or even death. Generally, there is limited information on the epidemiology of T. gondii of game species in Germany. As omnivores, raccoons, which are particularly widespread and abundant in Germany, are particularly exposed to infection the parasite. Here, we report the seroprevalence of T. gondii antibodies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
27
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(34 citation statements)
references
References 28 publications
5
27
2
Order By: Relevance
“…The values of 38.3% reported for raccoons ( Procyon lotor ) [ 16 ] and of 24.5% reported for the European mouflon ( Ovis orientalis musimon ) [ 17 ] were relatively high compared to values from other European studies in these species. These authors took this as evidence of high environmental contamination with oocysts as, in addition to the presence of feral, stray, and pet cats ( Felis sylvestris domesticus ), the study region was located within the core distribution area of the wildcat in central Germany [ 16 , 17 ]. Beral et al [ 4 ] found a positive link between higher T. gondii antibody levels in wild boar ( Sus scrofa ) and the occurrence of wildcats in France.…”
Section: Discussionmentioning
confidence: 78%
“…The values of 38.3% reported for raccoons ( Procyon lotor ) [ 16 ] and of 24.5% reported for the European mouflon ( Ovis orientalis musimon ) [ 17 ] were relatively high compared to values from other European studies in these species. These authors took this as evidence of high environmental contamination with oocysts as, in addition to the presence of feral, stray, and pet cats ( Felis sylvestris domesticus ), the study region was located within the core distribution area of the wildcat in central Germany [ 16 , 17 ]. Beral et al [ 4 ] found a positive link between higher T. gondii antibody levels in wild boar ( Sus scrofa ) and the occurrence of wildcats in France.…”
Section: Discussionmentioning
confidence: 78%
“…Our study area is indeed located within the core distribution area of the wildcat in central Germany [ 14 ]. Altogether, 38.3% of raccoons ( Procyon lotor ) sampled in the same study area were recently shown with a MAT test to be serologically positive for the protozoan [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Infection by the parasite may cause cerebral and ocular damage and even death, especially in immunodeficient patients [8,18]. Humans are mainly infected with T. gondii by ingesting uncooked meat and water contaminated by oocysts from the environment, or by vertical transmission [2,3,7]. In addition, T. gondii can also have a negative influence on animal growth, development and reproduction, and cause great economic loss to livestock husbandry [6].…”
Section: Introductionmentioning
confidence: 99%